Contribuições do escritório de projetos à gestão do portfólio de produtos - Jugend, Daniel; Barbalho, Sanderson César Macedo; Silva, Sergio Luis Da (Associação Brasileira de Engenharia de Produção, 2016)
Abstract Although many studies have investigated the project management office, and substantial research has also examined product portfolio management, few studies have analyzed these elements together. This paper aims to identify how the project management office can contribute to product portfolio management. The research consists of a case study at a high-tech company where the product portfolio is continuously renewed and that features a well-established project management office. Among the main results, it was observed that the project management office's participation is greater during portfolio review decisions than during decisions related to the strategic planning of products. Furthermore, the project management office supports top management and the project teams in applying financial methods and in the mapping and evaluation phases during product portfolio management activities.

Resumo Apesar de existirem muitos trabalhos sobre escritório de projetos e gestão de portfólio de produtos, são poucas as investigações que analisam esses elementos de maneira conjunta. Este artigo tem como objetivo identificar como o escritório de projetos pode contribuir com a gestão do portfólio de produtos. A pesquisa foi desenvolvida por meio de estudo de caso único em empresa de base tecnológica que renova seu portfólio de produtos com alta frequência e que possui a estrutura de escritório de projetos bem consolidada. Dentre os principais resultados, notou-se que é maior a participação do escritório de projetos nas decisões de revisão de portfólio do que naquelas relacionadas ao planejamento estratégico de produtos e que essa estrutura presta apoio à alta administração e às equipes de projeto para a aplicação dos métodos financeiros, de mapeamento e de avaliação de fases ao longo das atividades de gestão do portfólio de produtos.
Contributions of the project management office to product portfolio management
Keywords: Product portfolio management; Project management office; High-tech company; Gestão do portfólio de produtos; Escritório de projetos; Empresa de base tecnológica